Ultralow concentration of molybdenum disulfide nanosheets for enhanced oil recovery. (1st September 2019) - Raj, Infant; Qu, Ming; Xiao, Lizhi; Hou, Jirui; Li, Yongfeng; Liang, Tuo; Yang, Tianyuan; Zhao, Mengdan
Graphical abstract: Highlights: Alkylamine modified MoS2 nanosheets are promising for enhanced oil recovery. MoS2 nanosheets alter the wettability of the core even at very low concentrations. Residual oil recovery of 21.18% was obtained at 0.005 wt% of MoS2 nanofluid. MoS2 can recover even heavy oil from low-permeability cores. Abstract: Chemical enhanced oil recovery (C-EOR) agents, such as polymer and surfactants, have been used to recover residual oil from reservoirs. The investigation for finding more efficient and more economic agents has never been stopped. Here, we demonstrate the potential of two-dimensional MoS2 nanosheets as a C-EOR agent. The synthesized amphiphilic MoS2 nanosheets function as a surfactant by altering the wettability of the core even at very low concentrations. The laboratory core flooding experiments were performed in the man-made core samples with various permeabilities in range of 2.5–2500 mD saturated with crude oil (100 cP) and model oil (25 cP). The brine with the salinity of 98, 171 mg/L is used for secondary flooding and nanofluid containing 0.005 wt% of nanosheets is used for tertiary flooding. We observe 21.18% and 18.25% of residual oil is recovered during tertiary flooding in 25 mD core samples saturated with model and crude oil respectively. This work reveals the new possibilities for economical production of oil using nanosheet based materials.